(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
This study was conducted to evaluate dolomitization in the limestone rocks in upper cretaceous in Al-Querdaha sheet, Aljawbeh section. The study included 10 sites along 4km of the selected section, including field and analytical laboratory works. Samples were taken from the study site and a petrographic and geochemical study was carried out to illustrate the extent of the dolomitization spread in the region. An essay to link Dolomitization with hardness and quality of the rocks for construction purposes. Petrographic and geochemical study showed that dolomitization in the rocks of the region is partial dolomitization and dolomite here is Penecontemporaneous of low temperature (<50°C). Good rocks for construction purposes have low values of Sr and higher values of Mn, which may be related to high values of Mg.